2022
DOI: 10.1002/ijfe.2683
|View full text |Cite
|
Sign up to set email alerts
|

Trade credit and corporate growth

Abstract: While the underlying causal linkage between trade credit and corporate growth has mainly been explored, the primary factors that channel the relationship are limited. This article hypothesises a nonlinear relationship between trade credit and corporate growth due to the existing theoretical arguments on the benefit and cost of using suppliers' credit by corporations to enhance growth. Based on a panel of 23,023 non-financial companies from the United Kingdom over a 10-year period, evidence from this study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
0
0
0
1
Order By: Relevance
“…This suggests that the use of commercial credit requires a balance between benefit and cost for corporations to enhance their growth. In addition, it reflects the idea that the use of commercial credit is sensitive to financial constraints and financial crises [56,57]. It was also found that companies with more redistributable assets adjust their commercial credit relatively quickly compared to others [58].…”
Section: Funding Sources Applied For By Companiesmentioning
confidence: 55%
See 1 more Smart Citation
“…This suggests that the use of commercial credit requires a balance between benefit and cost for corporations to enhance their growth. In addition, it reflects the idea that the use of commercial credit is sensitive to financial constraints and financial crises [56,57]. It was also found that companies with more redistributable assets adjust their commercial credit relatively quickly compared to others [58].…”
Section: Funding Sources Applied For By Companiesmentioning
confidence: 55%
“…Commercial credit is the most important source of short-term financing for any company, and it can increase sales and profit [55]. A recent study [56] highlights the dominant role of commercial credit in corporate growth, underscoring a non-linear relationship between the use of commercial credit and corporate growth. This suggests that the use of commercial credit requires a balance between benefit and cost for corporations to enhance their growth.…”
Section: Funding Sources Applied For By Companiesmentioning
confidence: 99%
“…Para efectos del estudio, la entrevista se dio con el contador general de la empresa AFA GROUP de maquinaria y repuestos E.I.R.L., quien es la persona que está directamente relacionada con el área de créditos y cobranzas. Instrumentos Para Tingbani, et al [20] los instrumentos de investigación son como "los apoyos que tienen para que las técnicas cumplan su propósito. Se empleó como instrumento la guía de análisis de documentos, este instrumento nos permitirá conocer los informes, reportes y todos los documentos generales de la empresa que nos ayudarán a relacionar los objetivos planteados en la investigación, que serán detalladas en la interpretación de los resultados, para ello se utilizó el estado de situación financiera de la empresa de los periodos 2019, 2020 y 2021.…”
Section: Muestraunclassified
“…However, one of the most important issues is whether there is a linear relationship between trade credit and firm performance. Tingbani et al [2], examining the United Kingdom from 2005 to 2014, discovered a concave relationship between trade credit and corporate growth: it is positive at lower levels but negative at higher levels; moreover, while trade credit shows a positive response during financial crises, it supports the growth strategies of financially constrained firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trade credit (hereinafter referred to as trade credit investments) plays a vital role in providing financial assistance between firms, particularly during challenging times when obtaining external funding from banks and credit institutions becomes difficult [1,2]. Especially in developing and developed countries, trade credit holds a significant place in the balance sheets of companies.…”
Section: Introductionmentioning
confidence: 99%